The Impact of the Immune System on Tumor: Angiogenesis and Vascular Remodeling - Stockmann, Christian; Schadendorf, Dirk; Klose, Ralph; Helfrich, Iris (Frontiers in Oncology, 2014)
Angiogenesis, the formation of new blood vessels, as well as inflammation with massive infiltration of leukocytes are hallmarks of various tumor entities. Various epidemiological, clinical and experimental studies have not only demonstrated a link between chronic inflammation and cancer onset but also shown that immune cells from the bone marrow such as tumor-infiltrating macrophages significantly influence tumor progression. Tumor angiogenesis is a crucial step in tumor development as tumors have to establish a blood supply in order to grow and metastasize. Although tumor cells were first thought to drive the cellular events underpinning tumor angiogenesis, the use of transgenic mouse models and analysis of human tumor biopsies have shown that the tumor microenvironment with infiltrating immune cell subsets are important for regulating the process of tumor angiogenesis. These infiltrates involve the adaptive immune system including several types of lymphocytes as well as cells of the innate immunity such as macrophages, neutrophils, eosinophils, mast cells, dendritic cells and natural killer cells. Besides their known immune function, these cells are now recognized for their important role in regulating the formation and the remodeling of blood vessels in the tumor. In this review we will discuss for each cell type the mechanisms that regulate the vascular phenotype and its impact on tumor growth and metastasis.